MATHEMATICAL MODELLING AND SIMULATION OF FULL CAR SUSPENSION SYSTEM - Ranjit Rajale; Prof.K.K.Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
The objective of this paper is to mathematical modeling in relation with state space and eight degree freedom system of car seat and suspension system to determine set of parameters to maintain to achieve best condition of driver and occupants in vehicle. This index eliminates the need for further subjective estimations and can be a useful parameter in various correlation analyses and vibration comfort predictions. The vertical acceleration depends upon suspension parameters such as sprung mass, unsprung mass, stiffness of spring, damping coefficient and road profile. We have consider the passive type, constraints comes from practical and comfort ability considerations such as limit of vertical acceleration of passenger seat, tire displacement and suspension working space.